Novel Application of a Compound-Specific Stable Isotope (CSSI) Tracking Technique Demonstrates Connectivity Between Terrestrial and Deep-Sea Ecosystems via Submarine Canyons - Gibbs, Max; Leduc, Daniel; Nodder, Scott D.; Kingston, Andrew; Swales, Andrew; Rowden, Ashley A.; Mountjoy, Joshu; Olsen, Greg; Ovenden, Ron; Brown, Julie; Bury, Sarah; Graham, Brittany (Frontiers in Marine Science, 2020)
Studies have shown the importance of submarine canyons as conduits of land-derived organic carbon beyond the coastal shelf into the deep-sea where a single obvious river source can be identified. When there is more than one river source, identifying which rivers contribute to canyon sediment organic matter is technically challenging. Here, we compare two contrasting submarine canyons: the Hokitika Canyon, a long, narrow, and gently sloping canyon on the west coast of New Zealand; and the Kaikōura Canyon, a high productivity, short, steep canyon close to shore on the east coast of New Zealand. Both canyons have multiple potential river sources, so we applied a compound specific stable isotope (CSSI) tracking technique to identify and apportion the soil contribution from each river at locations along the length of each canyon axis. We found that land-derived carbon contributed between 74 to 100 % of the total organic carbon in the sediment of the Hokitika Canyon as far as 200 km from shore and to depths of 2000 m. However, less than 50% of the land-derived organic carbon came from the largest river closest to the canyon head. We hypothesise that longshore drift transported much of the sediment from that river past the Hokitika Canyon, while river inflows farther up-current supplied the bulk of the land-derived organic carbon. In contrast, land-derived carbon contributed less than 50% of the total organic carbon in Kaikōura Canyon sediments with land-derived organic sediment contribution decreasing steeply to less than 15% at about 24 km from shore in 1500 m water depth. Most of the land-derived organic matter (ca. 80%) came from the river with the largest suspended sediment yield, despite another (smaller) river discharging closer to the canyon head. We hypothesise that this difference in carbon source is partly due to the comparatively short and steep, and therefore dynamic, nature of Kaikoura Canyon resulting in efficient sediment through-put. The efficiency with which organic matter is captured and transferred to the deep-sea by canyons demonstrates the potential for such systems to act as natural carbon sinks driven by both geologically episodic and more regular oceanographic processes.